416 On-Call Junior Neurosurgery Residents Spend 9 Hours of Their On-Call Shift Actively Using the Electronic Health Record. (April 2023) - Patel, Arati; Zheng, Jeff; Rosner, Benjamin; Thombley, Robert; Sorour, Omar; Theodosopoulos, Philip V.; Aghi, Manish Kumar; Berger, Mitchel; Chang, Edward; Chou, Dean; Manley, Geoffrey; Mummaneni, Praveen V.; et al.
Abstract : INTRODUCTION: The Electronic Health Record (EHR) is central to clinical workflow, yet few studies to date have explored EHR usage patterns among neurosurgery trainees. METHODS: We utilized the EHR audit logs, time-stamped records of user activities, to review EHR usage of PGY-2 and 3 neurosurgery residents scheduled for 1 or more on-call days across 2 calendar years at the University of California San Francisco. We focused on the PGY-2 and 3 years, which in our training program represent the primary participants in the in-house on-call pool. RESULTS: Over 723 call days, 12 different residents took at least one on-call shift. The median (IQR) number of minutes that residents spent per on-call shift actively using the EHR was 536.8 (203.5), while interacting with an average (SD) of 68.1 (14.7) patient charts. There was no significant difference between active EHR time between residents as PGY-2 and PGY-3 on paired t-tests. Residents spent the most time on the following EHR activities: patient reports, notes, order management, patient list, and chart review. CONCLUSIONS: Residents spent, on average, 9 hours of their on-call shift actively using the EHR, and there was no improved efficiency as residents gained experience. We noted several areas of administrative EHR burden which could be reduced.